Evaluation of Structurally Integrated Surface Articulation (SISA) Panels for Architectural Engineering Applications - Yildirim, Feyza Nur (Mus Alparslan Üniversitesi, 2024)
This research explores the efficiency of a newly developed Structurally Integrated Surface Articulation (SISA) system for a variety of structural engineering applications, such as exterior building facades and solar panels. SISA is a modular system that consists of dynamically adjustable three-dimensional surface panels supported by an internal wire-frame space structure. The articulation techniques vary depending on the specific function of the panels, with configurations designed to optimize structural performance through composite action between the outer surface panels and the internal frame. Materials such as plastic, smart glass, and sheet metal are evaluated in conjunction with polyhedral and honeycomb configurations, including tetrahedral and convex polygonal forms. The research emphasizes enhancing large-scale structural efficiency by integrating modern frame systems with surface articulation. It also explores the evolution of architectural design and presents case studies using SISA-based structures to highlight the potential improvements in structural integrity. By addressing both material properties and design techniques, the study aims to demonstrate how the SISA system can provide significant advancements in architectural engineering.

Bu arastirma, dis cephe kaplamalari ve günes panelleri gibi çesitli yapisal mühendislik uygulamalari için gelistirilen yeni bir Yüzey Artikulasyonu ile Yapisal Olarak Entegre (SISA) sistemin verimliligini incelemektedir. SISA, içte bir tel-kafes yapi tarafindan desteklenen dinamik olarak ayarlanabilir üç boyutlu yüzey panellerinden olusan modüler bir sistemdir. Artikulasyon teknikleri, panellerin özel islevine bagli olarak degismekte ve dis yüzey panelleri ile iç yapi arasindaki kompozit etki sayesinde yapisal performansi optimize edecek sekilde yapilandirilmaktadir. Arastirmada plastik, akilli cam ve sac metal gibi malzemeler ile tetrahedral ve disbükey çokgen formlar gibi çokyüzlü ve petek konfigürasyonlar degerlendirilmektedir. Çalisma, modern çerçeve sistemlerini yüzey artikulasyonu ile entegre ederek büyük ölçekli yapisal verimliligi artirmayi vurgulamaktadir. Ayrica mimari tasarimin evrimini inceleyerek, SISA tabanli yapilari kullanarak yapisal bütünlükteki olasi iyilestirmeleri vurgulayan vaka çalismalarini sunmaktadir. Hem malzeme özelliklerini hem de tasarim tekniklerini ele alarak, bu çalisma SISA sisteminin mimari mühendislikte önemli gelismeler saglayabilecegini göstermeyi amaçlamaktadir.
Mimari Mühendislik Uygulamalari için Yapisal Olarak Entegre Yüzey Artikülasyon (SISA) Panellerinin Degerlendirilmesi
Keywords: Architectural Engineering; Mimari Mühendislik; Construction Materials; Yapi Malzemeleri